The efficacy and safety of irinotecan ± bevacizumab compared with oxaliplatin ± bevacizumab for metastatic colorectal cancer: A meta-analysis. Issue 39 (September 2019) - Dai, Jiali; Chen, Yuetong; Gong, Yang; Wei, Jingsun; Cui, Xiaowen; Yu, Hualin; Zhao, Wenjing; Gu, Dongying; Chen, Jinfei
Abstract: Background: Irinotecan (IRI)-based and oxaliplatin (OXA)-based regimens are available for the treatment of metastatic colorectal cancer (mCRC). Several studies have published inconsistent results in their comparisons of the efficacy and toxicity of IRI ± bevacizumab and OXA ± bevacizumab. This meta-analysis was performed to evaluate the efficacy and safety of these 2 regimens in patients with mCRC. Methods: We searched several databases to identify relevant studies, including PubMed, EMBASE, and the Cochrane Controlled Trials Register. The primary endpoints were overall survival (OS) and time to progression (TTP). The secondary comparisons were overall response rate (ORR) and toxicity. In addition, the hazard ratio (HR) or risk ratio (RR) values with their corresponding 95% confidence intervals (CIs) were extracted from these studies. Results: Pooled data of 13 studies demonstrated no significant differences in OS (HR = 0.96, 95% CI: 0.86–1.08, P = .53) and TTP (HR = 0.88, 95% CI: 0.72–1.08, P = .24) between the 2 groups. However, the ORR (RR = 0.87, 95% CI: 0.78–0.97, P = .02) was clearly improved in the OXA ± bevacizumab arm. Higher incidences of grade 3/4 nausea (RR = 1.63, 95% CI: 1.28–2.07, P < .001), vomiting (RR = 1.40, 95% CI: 1.09–1.81, P = .01), diarrhea (RR = 1.44, 95% CI: 1.23–1.70, P < .001), and anemia (RR = 4.13, 95% CI: 2.75–6.22, P < .001) were observed in the IRI group. However, the incidences of grade 3/4 neutropenia (RR = 0.75, 95% CI: 0.68–0.83, P < .001), thrombocytopenia (RR = 0.43, 95% CI: 0.26–0.73, P = .002), and paresthesia/neurological disturbances (RR = 0.04, 95% CI: 0.02–0.07, P < .001) were higher in the OXA group. Conclusion: This meta-analysis confirmed that the OXA ± bevacizumab regimen as a maintenance therapy significantly improved the ORR in patients with mCRC. Exhibiting strong efficacy and safety, the OXA and OXA plus bevacizumab regimens are preferred as first-line treatments for mCRC.